Motivation and Philosophical Objectives of the Islamic Economic System - Royani; Moh. Asep Zakariya Ansori; Hasan Bisri; Ija Suntana (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
This study intends to explore and examine the Islamic economic system in terms of its theoretical and philosophical foundations as well as its motivations and objectives. Like other disciplines, the Islamic economic system also has a philosophical foundation. The theoretical foundation of the sharia economic system certainly refers to the Al-Quran and hadith. At least QS an-Nisa verse 59 and the hadith of Mu'az bin Jabal can be used as a reference to determine the source of law that can be used as a legal basis for the basis of the existence of Islamic economics. Meanwhile, Islamic economic philosophy is based on three basic concepts, namely the philosophy of God, man (cosmic), and nature (cosmos). The key to Islamic economic philosophy lies in humans and God, humans and nature, as well as humans and other humans. The economic motivation in Islam is to make a living which is part of worship, not to pursue a hedonic life, not to pursue status let alone pursue wealth at all costs. While the goal of Islamic economics is also to uphold justice and brotherhood. The ultimate goal of Islamic economics is to achieve equity or balance in the distribution of income. The method used in this study is descriptive analysis which aims to get an overview of the foundation and philosophy as well as motivation and economic goals in Islamic economics.